2008
DOI: 10.4049/jimmunol.180.11.7553
|View full text |Cite
|
Sign up to set email alerts
|

PDL-1 Blockade Impedes T Cell Expansion and Protective Immunity Primed by Attenuated Listeria monocytogenes

Abstract: Infection with attenuated Listeria monocytogenes (Lm) is a robust in vivo model for examining how Ag-specific T cells are primed, and subsequent challenge with virulent Lm allows for the protective effects of T cell priming to be quantified. Herein, we investigated the role of programmed death ligand 1 (PDL-1) in T cell priming and immunity conferred after primary infection with Lm ΔactA followed by virulent Lm challenge. In striking contrast to the inhibitory role of PDL-1 on T cell immunity in other infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 28 publications
3
71
1
Order By: Relevance
“…In contrast to the results obtained in chronic viral infection models, where blockade of PD-1 induced increased effector functions in T cells, and more robust response against the pathogen, M. tuberculosis infection is fatal when the PD-1 pathway is rendered nonfunctional by gene deletion. Pathogen-related differences in PD-1 regulation have recently been indicated by a study showing that PD-L1 blockade suppressed antibacterial protection in infection with Listeria monocytogenes, suggesting a protective role for PD-L1 in antibacterial immunity (22,23). In addition, although PD-1 has been known to primarily regulate adaptive immune responses, such as T and B cell activation, two recent studies suggest that it could also regulate innate responses to bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the results obtained in chronic viral infection models, where blockade of PD-1 induced increased effector functions in T cells, and more robust response against the pathogen, M. tuberculosis infection is fatal when the PD-1 pathway is rendered nonfunctional by gene deletion. Pathogen-related differences in PD-1 regulation have recently been indicated by a study showing that PD-L1 blockade suppressed antibacterial protection in infection with Listeria monocytogenes, suggesting a protective role for PD-L1 in antibacterial immunity (22,23). In addition, although PD-1 has been known to primarily regulate adaptive immune responses, such as T and B cell activation, two recent studies suggest that it could also regulate innate responses to bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Our study adds that PD-1/PDL-1 regulation of CD8 T cell effector function is mediated locally by the epithelial cells of the lung, is regulated by IFNAR signaling, and can be therapeutically manipulated in the airways by intranasal administration of anti-PDL-1 blocking antibodies. Since PD-1 signaling has been shown to impact dendritic cell maturation, antigen presentation, and T cell priming and expansion (34,(42)(43)(44), it is important to differentiate the systemic role of PD-1/ PDL-1 during the generation of adaptive immune responses from the specific role at the mucosal site of infection during epithelial-T cell interaction cross talk.…”
Section: Discussionmentioning
confidence: 99%
“…Ni and colleagues concluded that the outcome of the PD-L1-mediated effect on CD8 + T cells depends on whether CD4 + T cells are present, the nature of the interacting partner expressed by CD8 + T cells, and the tissue microenvironment. immunity against infection with Listeria monocytogenes (19) and Salmonella (20). It has also been shown that PD-L1 expression by activated antigen-specific CD8 + T cells is required for their survival following expansion through both the inhibition of apoptotic T cell death by increasing levels of the antiapoptotic protein BCL-xL and by decreasing T cell-T cell fratricide (21).…”
Section: Gvl Versus Gvhdmentioning
confidence: 99%